Odpowiedź:
Szczegółowe wyjaśnienie:
a) 2x - 7 = x + 5 x=12
2·12-7=12+5
24-7=17
17=17
b) x²-x=5 x=12
12²-12=5
144 -12=5
132=5
c) 2(x-7) =x-1 x=13
2·13-7=13-1
26-7=12
19=12
d) x/2-5=6 x=12
6-5=6
1=6
e)4x-8=28 x=10
4·10-8=28
32=28
f) 1/3x-5=2x-5 x=9
1/3·9-5=18-5
3-5=13
-2=13
g) x(x-2)=x+1 x=-3
(-3)·((-3)-2)=(-3)+1
(-3)·(-5)=(-2)
15=(-2)
h) 3x-8(x+1)=1 x=-2
(-6)-8·((-2)+1)=1
(-14)·(-1)=1
14=1
i) x11-x/12=0 x=0
0=0
j) x2020-x2019+x2018=1 x=1
(-1)·2020-(-1)·2019+(-1)·2018=1
(-2020)+2019-2018=1
Mam nadzieję, że pomogłam :)